Transporte de material particulado em suspensão em um estuário dominado por maré: estuário do rio Mojuim São Caetano de Odivelas-Pará - MEDEIROS, Paula Renata Lobato de (2019)
This study aims to evaluate whether there are seasonal differences in the transport of suspended particulate matter, depending on the tide and rainfall on the estuary of Mojuim river located in São Caetano de Odivelas (Northeast Pará), which is an estuarine system shallow characterized by high concentration of MPS. This estuarine system is strongly influenced by macrotidal regime, which promote changes in the concentration of suspended particulate matter (SPM) and, consequently, result in different morphological changes along the river. To quantify the MPS concentrations (gravimetric method) were collected 65 samples the water surface and bottom, with the aid of an Oceanographic bottle type Van Dorn, at a tidal cycle in three sampling stations in a transect the shores (MD), left (ME) and mid-channel (M). The data was obtained from hydrodynamic with the aid of a ADCP. MPS concentrations showed seasonal variations with an average of 45.8 mg / L in the shortest period of rainfall and 50.0 mg / L in most rainfall period, these variations were also observed in MPS transportation. The estuary of the river is Mojuim pellet exporter in both periods, being transported about 5.25 to 5630 tonnes and the period of greatest rainfall export was 6.5 to 7.9 tonnes of MPS.